Pan-Cancer Analysis of the Cuproptosis-Related Gene DLD - Jiahui Lin; Guowei Wang; Sha Cheng; Yanan Hu; Huan Li; Wanjiang Feng; Xiaoming Liu; Canxia Xu (Mediators of Inflammation)
Background. Cancer affects millions of people each year and imposes a huge economic and social burden worldwide. Cuproptosis is a recently discovered novel mode of cell death. The exact function of the cuproptosis-related gene dihydrolipoamide dehydrogenase (DLD) and its role in pan-cancer is unknown. Methods. Data were retrieved from the GTEx, TCGA, and multiple online websites. These data were used to assess the expression, prognosis, and diagnostic value of DLD in various tumors. The relationship of DLD with immune microenvironment immunomodulators, immune checkpoints, tumor mutational load (TMB), microsatellite instability (MSI), and oncology drug sensitivity was explored by correlation analysis. Results. The mRNA and protein expression of DLD differs in most cancers. Survival analysis showed that DLD was associated with prognosis with KIRC, KIRP, KICH, and UCS. DLD had a strong diagnostic value in KIRC, GBM, PAAD, and LGG (AUC > 0.9). DLD promoter methylation affects the aberrant expression of LIHC, LUSC, PAAD, READ, and THCA. DLD was negatively correlated with stromal score, immune score, and ESTIMATE score in UCEC, TGCT, LUSC, and SARC. In UCS, resting memory CD4 T cells and activated NK cells were significantly correlated with DLD expression. Significant correlations were also observed between DLD expression and immunomodulators, immune checkpoints, TMB, and MSI in various cancers. Importantly, we also identified a number of potential drugs that may target DLD. Conclusion. DLD expression is associated with a variety of tumor prognoses and plays an integral role in tumorigenesis, tumor metabolism, and immunity.